2010
DOI: 10.1177/0956797610372632
|View full text |Cite
|
Sign up to set email alerts
|

Watching Film for the First Time

Abstract: Although film, television, and video play an important role in modern societies, the extent to which the similarities of cinematographic images to natural, unmediated conditions of visual experience contribute to viewers' comprehension is largely an open question. To address this question, we compared 20 inexperienced adult viewers from southern Turkey with groups of medium- and high-experienced adult viewers from the same region. In individual sessions, each participant was shown a set of 14 film clips that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 16 publications
0
22
1
Order By: Relevance
“…There are filmic cuts, camera pans, and temporal ellipses. Although research has shown that filmic cuts including abrupt viewpoint changes hinder visual processing and affect memory for artificial dynamic scenes (Garsoffky, Huff, & Schwan, 2007;Huff, Jahn, & Schwan, 2009;Huff, Meyerhoff, Papenmeier, & Jahn, 2010), there is some evidence that experienced viewers have no problems in following a plot despite severe disruptions of the perceptual process (Germeys & d'Ydewalle, 2007;Huff & Schwan, 2012;Schwan & Ildirar, 2010;Smith & Henderson, 2008). Further, filmic cuts might disrupt the depicted action.…”
Section: Discussionmentioning
confidence: 97%
“…There are filmic cuts, camera pans, and temporal ellipses. Although research has shown that filmic cuts including abrupt viewpoint changes hinder visual processing and affect memory for artificial dynamic scenes (Garsoffky, Huff, & Schwan, 2007;Huff, Jahn, & Schwan, 2009;Huff, Meyerhoff, Papenmeier, & Jahn, 2010), there is some evidence that experienced viewers have no problems in following a plot despite severe disruptions of the perceptual process (Germeys & d'Ydewalle, 2007;Huff & Schwan, 2012;Schwan & Ildirar, 2010;Smith & Henderson, 2008). Further, filmic cuts might disrupt the depicted action.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study has shown that there is a difference between first time film viewers and experienced viewers in understanding viewpoint changes within a scene (Schwan & Ildirar, 2010). Whereas experienced viewers do understand such viewpoint changes first time viewers do not.…”
Section: Discussionmentioning
confidence: 98%
“…In light of a recent study with film-illiterate viewers, which demonstrated that comprehending spatial relations between adjacent shots requires sufficient familiarity with films (Schwan & Ildirar, 2010), the interplay of the centerline rule and the spatial heuristic may be interpreted as a convention or as a kind of "contract" between filmmaker and viewer. We also speculate that the applicability of this heuristic instead of computationally demanding realignment is one of the reasons why sequences of shots in films are often experienced as continuous and film cuts often go unnoticed by the viewers (T. J.…”
Section: Discussionmentioning
confidence: 99%